Return to Activities of Daily Living after Breast Cancer Surgery: An Observational Prospective Questionnaire-Based Study of Patients Undergoing Mastectomy with or without Immediate Reconstruction - L. Ballance; R. L. Wilson; C. C. Kirwan; G. Boundouki; V. P. Taxiarchi; B. G. Baker; V. Rusius; M. Rowland; J. R. Henderson; N. Marikakis; J. McAleer; J. R. Harvey; et al. (The Breast Journal)
Background. Patients often ask about the time taken to return to activities of daily living (ADLs) after breast surgery, but there is a lack of data to give accurate guidance. We aimed to assess the feasibility of a study to determine the time taken to return to ADLs after mastectomy with or without breast reconstruction. Materials and Methods. A prospective multicentre, self-reported questionnaire-based feasibility study of women who had undergone mastectomy ± reconstruction was performed, between Jan 2017 and Dec 2019. Women were asked to self-report when they returned to 15 ADLs with a 5-option time scale for “return to activity.” Results. The questionnaire was returned by 42 patients (median [range] age: 64 [31–84]). Of these, 22 had simple mastectomy, seven mastectomy and implant reconstruction, seven mastectomy and autologous reconstruction (DIEP), and six did not specify. Overall, over 90% could manage stairs and brush hair by two weeks and 84% could get in and out of the bath by four weeks. By 1-2 months, 92% could do their own shopping and 86% could drive. 68% of women employed returned to work within four months. Compared to simple mastectomy, patients undergoing reconstruction took a longer time to return to getting in/out of bath (<2 vs. 2–4 weeks), vacuuming (2–4 weeks vs. 1-2 months), and fitness (1-2 vs. 3-4 months). There was a slower return to shopping (1-2 months vs. 2–4 weeks), driving and work (both 3-4 vs. 1-2 months), and sports (3-4 vs. 1-2 months) in autologous reconstruction compared to implant reconstruction. Conclusion. This study is feasible. It highlights slower return to specific activities (particularly strength-based) in reconstruction patients, slower in autologous compared with implant reconstruction. The impact on return to ADLs should be discussed as part of the preoperative counselling as it will inform patients and help guide their decision making. A larger study is required to confirm these results.